Elucidating thoracic aortic dissection pathogenesis: The interplay of m1A-related gene expressions and miR-16-5p/YTHDC1 Axis in NLRP3-dependent pyroptosis - Liu, Kun; Li, Yuemeng; Yin, Fanxing; Wu, Xiaoyu; Zhang, Xiaoxu; Jiang, Deying; Wang, Jian; Zhang, Zhaoxuan; Wang, Ruihua; Chen, Chen; Han, Yanshuo (International journal of biological macromolecules, 2024)
The underlying molecular mechanisms of thoracic aortic dissection (TAD) remain incompletely understood. Recent insights into RNA methylation and microRNA-mediated gene regulation offer new avenues for exploring how these processes contribute to the pathophysiology of TAD, particularly through the modulation of pyroptosis and smooth muscle cell viability. This research aimed to elucidate the interplay of m1A-related gene expressions and miR-16-5p/YTHDC1 Axis in NLRP3-dependent pyroptosis, a mechanism implicated in the pathogenesis of TAD. We collected tissue samples from 28 human TAD patients and 8 healthy aortic group, as well as utilized a mouse model to replicate the disease. A combination of computational, in vitro, and in vivo methods was applied, including CIBERSORTx analysis, Pearson correlation, gene transfection using antagomiR-16-5p, siRNA, and several staining as well as cell culture techniques. Our analysis indicated two differentially expressed genes, ALKBH2 and YTHDC1. We found significant upregulation of has-miR-16-5p and downregulation of YTHDC1 at mRNA level in AD samples. Immune cell infiltration in TAD samples was examined using the CIBERSORTx database. We confirmed that YTHDC1 was a target of miR-16-5p, as evidenced by an inhibitory effect on luciferase activity. Inhibition of miR-16-5p enhanced SMC proliferation and promoted cell viability whilst downregulating NLRP3-pyroptosis. YTHDC1 expression was increased, and NLRP3-pyroptosis expressions were inhibited, suggesting miR-16-5p/YTHDC1 axis may involve the NLRP3-pyroptosis of the SMC. In vivo analyses confirmed the prevention of NLRP3-pyroptosis in middle layer of the thoracic aorta, implying that the miR-16-5p/YTHDC1 axis regulated SMC proliferation via NLRP3-pyroptosis signaling. Our findings underscored the anti-pyroptotic role of miR-16-5p/YTHDC1 axis in the pathogenesis of TAD, suggesting a potential therapeutic strategy via targeting YTHDC1 and suppressing miR-16-5p to inhibit NLRP3-dependent pyroptosis. Although further investigation is needed, these results relating to SMC proliferation are a significant step forward in understanding TAD.